The performance of a bench scale liquefaction of carbon dioxide - Abdul Latif, Nur Hidayah; Nasir Ani, Farid; Hamdan, Halimaton (Faculty of Mechanical Engineering, 2009)
Presently, the use of liquefied carbon dioxide in research centers and industry is becoming important due to the various research activities and applications in industry. The aim of this work is to liquefy carbon dioxide gas insitu using an appropriate cryogenic system. Carbon dioxide is non-toxic, non-flammable, has zero ozone depletion potential and negligible global warming potential as refrigerant as compared to hydrocarbon and freon gases. The analysis has been carried out using a bench scale liquefaction test rig, with capacity of about 1 kg/min. The test rig operates at condensing pressures between 50 to 120 bar and chiller temperatures between -15 to 7oC in order to produce the liquid carbon dioxide. Liquified carbon dioxide has many applications, such as refrigerant, fire extinguishing agent, supercritical extraction fluid and in the beverage industry. The properties of carbon dioxide at different states of the liquidification process are obtained from the property diagram and are used to evaluate the performance of the liquefaction bench scale test rig